Lohkoketjujen potentiaali ja tulevaisuus - Seppänen, Erno (2018)
The blockchain technology is a foundational and disruptive phenomenon, which intends to revolutionize technologic development with its sosionomic advantages. Blockchain attracts a lot of attention with its most used applications, smart-contracts and cryptocurrencies and new applications are born constantly. The hindering aspects of blockchain development are vast amount new terms along with their notions. On top of that, the code itself is vulnerable to attacks and government regulations take place in many countries. The research is focused mainly on Bitcoin and not so much in blockchain applications and potential. In spite of all that, blockchain as a technology will digitalize our society to a new sphere.